Analysis of Factors Affecting The Timeliness of Financial Reporting on Manufacturing Companies in The Indonesia Stock Exchange - Jalilah Ilmiha; Lusi Elviani Rangkuti; Farida Khairani Lubis (PT. EQUATOR SINAR AKADEMIA, 2022)
This study aims to find empirical evidence about the factors that affect the timeliness of financial reporting of manufacturing companies listed on the Indonesia Stock Exchange. The research uses quantitative research methods. The data collected in this study will be analyzed using two methods, namely 1) Descriptive statistical method, the analytical tool used is the average (mean) and standard deviation 2) Hypothesis Testing, hypothesis testing is done by using multivariate test using logistic regression. The sample from this study used 43 manufacturing companies x in 3 years of research, 129 data on financial statements that were consistently listed on the Indonesia Stock Exchange for the period 2014-2016 were taken using the purposive sampling method. Based on Simultaneous Effect Analysis, it can be seen that α= 0.05 and degrees of freedom (df) = k = 5, where k is the number of predictor variables, the value of χ²(p) from the chi-square distribution table is 11.07048. Due to 6.266 < 11.07048 or -2(L0–L1) < χ²(p), it can be said that together (simultaneously), the five predictor variables (DER, ROA, SIZE, KAP, AUDCH) have no effect on the variable of timeliness of financial reporting.